Athlete data sovereignty: addressing the legal and policy gaps in sports technology - Kwon, J. W. (Frontiers in Sports and Active Living, 2025)
Sports technology has rapidly reshaped the measurement and governance of athletic performance. Wearables, smart fabrics, and AI-linked sensors now generate constant biometric and tactical streams used for analytics, injury prevention, and fan-facing applications. As these tools become embedded in everyday training, the line between assistance and surveillance becomes harder to distinguish, raising new concerns about autonomy and control (1). Although the data originate from athletes` bodies, legal ownership remains uncertain (2). Existing privacy law and international sports governance frameworks offer no clear allocation of rights over the digital traces produced through play or training (3). The concept of data sovereignty-first developed in Indigenous data governance and later expanded into digital rights debates-suggests that individuals should retain authority over information tied to their bodily identity (4). Yet, despite its relevance, this principle has rarely been applied to the sporting context (5). This absence of legal clarity creates a paradox. Athletes generate the data that underpin modern sports technology, yet remain largely excluded from decision-making about its use. Without a recognised ownership framework, performance data sit in an ambiguous space: deeply personal yet institutionally controlled, private yet commercially valuable (6).